HUBUNGAN ANTARA RELIGIUSITAS KEISLAMAN DENGAN RITUAL PENGRAWIT PADA MAHASISIWA ISI SURAKARTA - Prasetyo, Andy Irawan (TALENTA, 2013)
Mostly Indonesian people are moslem but still thick with cultural traditions. More traditions can be found in rural areas than in urban areas that have historically and practically became a center of administration and authorities. This phenomenon is a manifestation of attitudes and behaviors reqarding matters that are considered sacred, holy, and comes from spiritual matters. For communities, the manifestation of an intrinsic sense ofÂ  responsibility. Ritual tradition is a real media and a symbol of social media. Individual religiosity helped maintain the psychological health of individuals in difficult times. The result shows : (1) there is avery significant positive relationship between Islamic ritual with attitudes towards pengrawit ritual. This is indicated by the results of the correlation coefficient (r) = 0,998 with p=0,000 (p<0,01). (2) Islamic religiosity variables empirical average = 106,59 and the hypothetical average = 90 thus the ability to empathize with the subject of research high. (3) attitudes towards ritual pengrawit category with empirical average 112,79 and hypothetical average = 90. (4) Effectiveness contribution of Islamic religiosity 98,8% towards ritual pengrawit attitudes, shown from determination coefficient (rÂ²)=0,988. There are 1,1% can be influenced by other factors side thus variable.